DNA diversity among clinical isolates of Helicobacter pylori detected by PCR-based RAPD fingerprinting. - Akopyanz, N (1992)
The RAPD (or AP-PCR) DNA fingerprinting method was used to distinguish among clinical isolates of Helicobacter pylori, a bacterium whose long term carriage is associated with gastritis, peptic ulcers and gastric carcinomas. This method uses arbitrarily chosen oligonucleotides to prime DNA synthesis from genomic sites to which they are fortuitously matched, or almost matched. Most 10-nt primers with > or = 60% G + C yielded strain-specific arrays of up to 15 prominent fragments, as did most longer (> or = 17-nt) primers, whereas most 10-nt primers with 50% G+C did not. Each of 64 independent H. pylori isolates, 60 of which were from patients in the same hospital, was distinguishable with a single RAPD primer, which suggests a high level of DNA sequence diversity within this species. In contrast, isolates from initial and followup biopsies were indistinguishable in each of three cases tested.